Exploring the interplay between guidance services and career success: Unveiling the key determinants? - Paul Mensah Agyei; Joyce Kwakyewaa Dankyi; Vincent Mensah Minadzi; Lydia Aframea Dankyi; Moses Segbenya (PLoS ONE, 2025)
This study examines the effect of determinants of stakeholders’ attitudes on the perceived relevance of guidance services, policy implementation, and career success. An explanatory research design was adopted for the study. A sample of 413 guidance service coordinators at the regional, district, and school levels were selected. A self-developed questionnaire was used for the data collection. It was found that the availability of funds (finance) for payment of expenses incurred in relation to guidance services, competent and adequate guidance coordinators, and a dedicated office to ensure confidentiality for guidance services were the three determinants that predicted the perceived relevance of guidance services in Ghana. Additionally, provisions for guidance services on the teaching timetable, availability of logistics (material resources), and quality guidance coordinators were the only three determinants that influenced policy implementation and monitoring of guidance services at the basic school levels in Ghana. Human resources again emerged as the only determinant that influenced the career success of beneficiaries in Ghana. The study recommends that Ghana Education Service and heads of basic schools should appoint competent and adequate guidance service coordinators, resource them financially and logistically, allocate guidance services on the teaching timetable, and provide a dedicated office to ensure confidentiality.